Short-Term Neonatal Outcomes in Diamniotic Twin Pregnancies Delivered after 32 Weeks and Indications of Late Preterm Deliveries - Shamshirsaz, Alireza A.; Ravangard, Samadh F.; Ozhand, Ali; Haeri, Sina; Shamshirsaz, Amirhoushang A.; Hussain, Naveed; Spiel, Melissa; Ogunleye, Oluseyi; Billstrom, Rachel; Sadowski, Alison; Turner, Garry; Timms, Diane; Egan, James F. X.; Campbell, Winston A. (American Journal of Perinatology, 2014)
Objective We sought to compare neonatal outcomes in twin pregnancies following moderately preterm birth (MPTB), late preterm birth (LPTB), and term birth and determine the indications of LPTB.Study Design We performed a retrospective cohort study. MPTB was defined as delivery between 320/7 and 336/7 weeks and LPTB between 340/7 and 366/7 weeks. The composite neonatal adverse respiratory outcome was defined as respiratory distress syndrome and/or bronchopulmonary dysplasia. The composite neonatal adverse nonrespiratory outcome included early onset culture-proven sepsis, necrotizing enterocolitis, retinopathy of prematurity, intraventricular hemorrhage, or periventricular leukomalacia. LPTB cases were categorized as spontaneous (noniatrogenic), evidence-based iatrogenic, and non-evidence-based (NEB) iatrogenic.Results Of the 747 twin deliveries during the study period, 453 sets met the inclusion criteria with 22.7% (n = 145) MPTB, 32.1% (n = 206) LPTB, and 15.9% (n = 102) term births. Compared with term neonates, the composite neonatal adverse respiratory outcome was increased following MPTB (relative risk [RR] 24; 95% confidence interval [CI] 3.0 to 193.6) and LPTB (RR 13.7; 95% CI 1.8 to 101.8). Compared with term neonates, the composite neonatal adverse nonrespiratory outcome was increased following MPTB (RR 22.3; 95% CI 3.9 to 127.8) and LPTB (RR 5.5; 95% CI 1.1 to 27.6). Spontaneous delivery of LPTB was 63.6% (n = 131/206) and the rate of iatrogenic delivery was 36.4% (n = 75/206). The majority, 66.6% (n = 50/75), of these iatrogenic deliveries were deemed NEB, giving a total of 24.2% (50/206) NEB deliveries in LPTB group.Conclusion Our data demonstrate a high rate of late preterm birth among twin pregnancies, with over half of nonspontaneous early deliveries due to NEB indications. Although our morbidity data will be helpful to providers in counseling patients, our finding of high NEB indications underscores the need for systematic evaluation of indications for delivery in LPTB twin deliveries. Furthermore, this may lead to more effective LPTB rate reduction efforts.
Keywords: diamniotic twin; neonatal outcomes; late preterm births; moderately preterm births